Enhanced As(III) removal from aqueous solution by Fe-Mn-La-impregnated biochar composites - Lin, Lina; Song, Zhengguo; Khan, Zulqarnain Haider; Liu, Xuewei; Qiu, Weiwen (The Science of the total environment, 2019)
A novel Fe-Mn-La-impregnated biochar composite (FMLBC) was synthesized using an impregnation method for efficient As (III) adsorption. The pseudo-second-order model (R2 values are 0.996, 0.996, and 0.994 for different FMLBC rate used) better fitted the kinetic adsorption of arsenic (As) on the FMLBC than the pseudo-first order model (R2 values are 0.978, 0.971, and 0.991 respectively). The SEM-EDS, FTIR and XPS results confirmed the addition of Fe, Mn and La into the BC structure. Compared with pristine biochar (3.73 mg g−1) and Fe-Mn-impregnated biochar (9.48 mg g−1), the As (III) adsorption capacity of Fe-Mn-La impregnated biochar (14.9 mg g−1) was significantly improved. The presence of NO3− and SO42− did not influence As adsorption, whereas PO43− influenced As removal. The mechanism of As adsorption on the FMLBC involved oxidization, electrostatic attraction, ligand exchange, and formation of an inner-sphere R-O-As complex. Among them, the electrostatic attraction and inner-sphere complexation contributed the most. The simple preparation process and high adsorption performance suggest that the FMLBC could be served as a promising adsorbent for As (III) removal from aqueous solution. [Display omitted] •Fe-Mn-La impregnated biochar (FMLBC) was prepared through an easily synthetized method.•As (III) adsorption capacity of Fe-Mn-La impregnated biochar (14.9 mg g−1) was significantly improved.•The adsorption mechanism of arsenic is mainly electrostatic attraction and inner-sphere complexation.•LaO plays an important role in As adsorption due to formation of La-O-As complex.